Improved risk stratification by PET-based intratumor heterogeneity in children with high-risk neuroblastoma - Li, Chao; Wang, Shaoyan; Li, Can; Yin, Yafu; Feng, Fang; Fu, Hongliang; Wang, Hui; Chen, Suyun (Frontiers in Oncology, 2022)
Purpose: Substratification of high-risk neuroblastoma is challenging, new predictive imaging biomarkers are warranted for better patient selection. The aim of the study was to evaluate the prognostic role of PET-based intratumor heterogeneity and the potential ability to improve risk stratification in neuroblastoma. Methods: Pretreatment 18F-FDG PET/CT scans from 112 consecutive children with newly diagnosed neuroblastoma were retrospectively analyzed. The primary tumor was segmented in the PET images. SUVs, volumetric parameters including metabolic tumor volume (MTV) and total lesion glycolysis (TLG), and texture features were extracted. After exclusion of imaging features with poor and moderate reproducibility, relationships between the imaging indices and clinicopathological factors, as well as event-free survival (EFS) were assessed. Results: The median follow-up duration was 33 months. Multivariate analysis showed that PET-based intratumor heterogeneity outperformed clinicopathological features, including age, stage, MYCN, and remained the most robust independent predictor for EFS [training set, hazard ratio (HR), 6.4, 95% CI: 3.1-13.2, p < 0.001; test set, HR, 5.0, 95% CI, 1.8-13.6, p = 0.002]. Within the clinical high-risk group, patients with a high metabolic heterogeneity showed significantly poorer outcomes (HR, 3.3, 95% CI, 1.6-6.8, p = 0.002 in the training set; HR, 4.4, 95% CI, 1.5-12.9, p = 0.008 in the test set) compared to those with relatively homogeneous tumors. Furthermore, intratumor heterogeneity outran the volumetric indices (MTVs and TLGs), and yielded the best performance of distinguishing high-risk patients with different outcomes with a 3-year EFS of 6% vs. 47% (p = 0.001) in the training set and 9% vs. 51% (p = 0.004) in the test set. Conclusion: PET-based intratumor heterogeneity was a strong independent prognostic factor in neuroblastoma. In the clinical high-risk group, intratumor heterogeneity further stratified patients with distinct outcomes.